TRANSFORMASI PENGGUNAAN CRYPTOCURRENCY MELALUI BITCOIN DALAM TRANSAKSI KOMERSIAL DIHUBUNGKAN DENGAN DISKURSUS PERLINDUNGAN HUKUM (LEGAL PROTECTION) KONSUMEN DI INDONESIA - Itok Dwi Kurniawan; Satryo Sasono; Ismawati Septiningsih; Bambang Santoso; Harjono Harjono; Muhammad Rustamaji (Jurnal Hukum Mimbar Justitia, 2021)
The Payment methods and electronic transaction in commercial activities in Indonesia are experiencing rapid development, Financial Technology (fintech) which carries the payment platform has begun to shift towards Virtual Currency as a virtual currency. E-Commerce is the reason why people's needs for changing payment methods into virtual currencies take a big role, one of which is through Bitcoin as a cryptographic-based virtual currency which has experienced significant development since it was marketed in 2009. The writing of this article uses legal research normative, namely by describing, analyzing some of the existing problems, then re-elaborating using a study based on legal concept and theories based on Law. This article will review the clarity of Bitcoin as a virtual currency as well as a legal payment medium and describe its legality with related legal norms and the presence of the Commodity Futures Trading Law as the most important regulation new existence of Bitcoin in Indonesia.Keywords: Cryptocurrency, Legal Consument Protection, Bitcoin